2007
DOI: 10.1021/np0604681
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Triterpenoid Saponins from Ardisia japonica

Abstract: Eleven new triterpenoid saponins, ardisianosides A (1), B (2), C (4), D (5), E (6), F (7), G (15), H (16), I (17), J (18), and K (19), together with 10 known saponins, were isolated from the whole plants of Ardisia japonica. The structures of the new saponins were established on the basis of extensive 1D and 2D NMR and MS studies coupled with chemical degradations. The cytotoxic activities of saponins 1-21 are reported against three human cancer cell lines, namely, HL-60 myeloid leukemia, KATO-III stomach aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 16 publications
(86 reference statements)
0
71
0
Order By: Relevance
“…Furthermore, the oleanolic acid of 1 was obtained by acid hydrolysis, and was identified by ESIMS and NMR analysis. (Chang et al, 2007). For the rhamnose unit, the large 1 J C1, H1…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the oleanolic acid of 1 was obtained by acid hydrolysis, and was identified by ESIMS and NMR analysis. (Chang et al, 2007). For the rhamnose unit, the large 1 J C1, H1…”
Section: Resultsmentioning
confidence: 97%
“…In the 1 H NMR spectrum, an oxymethine proton at δ 3.50 (dd, J=11.6, 4.3 Hz, H-3) was coupled to two other protons and from decoupling experiments, it was shown to be part of -CH2-CH-(O-glc)-C(CH3)2-CH-system analogous to the C-2 to C-5 region in oleanane skeleton. 18 This allowed the oligosaccharide attached to the aglycone to be assigned to C-3 where it is in equatorial configuration, a fact further supported by the HMBC cross-peak between H-1' (δ 4.72) and C-3 (δ 80.1), and confirmed by NOESY cross-peaks between H-3 and Me-23 (δ 1.14 s) and also in turn with H-5.…”
mentioning
confidence: 76%
“…Hence, sequence of saccharide moiety was evaluated as 13 C NMR peaks at δ 180.4 (C-28) and 92.6 (C-13) suggested that the aglycone is an oleanane derived triterpenoid (C30) skeleton with oxygen functionalities in positions C-3, C-16, C-21 and C-22 in addition to the epoxy-γ-lactone moiety at C-13 and C-28. 18 The presence of the latter functionality was further supported by IR spectrum characteristic peaks at 1758 and 875 cm -1 . 24,25,26 The downfield shift of the 1 H NMR signal at δ 4.96 suggested the presence of an acetyl group and was confirmed by HMBC cross-peak between the H-22 (δ 4.96) and δ 171.0 (acetyl group) to be at C-22.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The previous research on chemical constituents of D. carota has carried out the presence of sesquiterpenes, [6][7][8] chromones, 9) flavonoids, 10,11) coumarins 6,12) and anthocyanins. 13,14) As a part of our ongoing investigation on bioactive constituents, [15][16][17][18] we initiated a phytochemical investigation on the fruits of D. carota L., which resulted in the isolation of two new guaiane-type sesquiterpene glycosides, 11-O-acetyl-torilolone 8-O-b-D-glucopyranoside (1) and 1b-hydroxytorilolone 11-O-b-D-glucopyranoside (2). In this paper, we report the isolation and structure elucidation of them.…”
Section: Notesmentioning
confidence: 99%